Effectiveness of Eye Movement Desensitization and Reprocessing in German Armed Forces Soldiers With Post-Traumatic Stress Disorder Under Routine Inpatient Care Conditions. Issue 5 (1st May 2017) - Köhler, Kai; Eggert, Patrick; Lorenz, Sebastian; Herr, Kerstin; Willmund, Gerd; Zimmermann, Peter; Alliger-Horn, Christina
ABSTRACT: Background: Post-traumatic stress disorder (PTSD) is one of the more commonly occurring mental disorders following potentially traumatizing events soldiers may encounter when deployed abroad. One of the first-line recommended treatment options is eye movement desensitization and reprocessing (EMDR). The number of studies assessing the effectiveness of EMDR in German soldiers under routine conditions is currently almost nil. Methods: A retrospective, quasi-experimental effectiveness study on EMDR in an inpatient setting is presented using a prepost design. The study compares symptom reduction in soldiers ( N = 78) with a wait-list ( N = 18). Effect sizes of EMDR were measured for PTSD, symptoms of depression, and general mental health. Results: Effect size for EMDR treatment of PTSD was d = 0.77; 95% confidence interval (CI): 0.51 to 1.36, for symptoms of depression d = 0.99; 95% CI: 0.31 to 1.36, and for general psychiatric symptoms d = 0.53; 95% CI: 0.17 to 1.21. The effects resulting from EMDR treatment were somewhat weaker than those reported in comparable studies in civilians. Conclusion: EMDR therapy is an effective treatment to reduce symptoms of PTSD and depression. However, in the military context it needs to be complemented by treatment options that specifically address further conditions perpetuating the disorders.